Patient with D transposition of Great Arteries Operated by Senning Procedure: A Case Report - Hoque, Ashraful; Moinuddin, Shahriar (Journal of Current and Advance Medical Research, 2018)
The atrial switch operation, the Mustard or Senning operation, for the transposition of the great arteries (TGA) was introduced in the late 1950s and was the preferred surgery for TGA until the early 1990s. The arterial switch operation has become the procedure of choice for patients with transposition of the great arteries (TGA) in most medical centres. Although atrial switching may occasionally be employed in some centres in cases with delayed diagnosis, pulmonary hypertension and some other unusual entities. We preferred to use the atrial switch operation Senning procedure for 5 months old child with TGA, small atrial septal defect (ASD) and patent ductus arteriosus (PDA). Journal of Current and Advance Medical Research 2017;4(1):31-33